Tai Chi practice enables prefrontal cortex bilateral activation and gait performance prioritization during dual-task negotiating obstacle in older adults - Chen, Yan; Wan, Aiying; Mao, Min; Sun, Wei; Song, Qipeng; Mao, Dewei (Frontiers in Aging Neuroscience, 2022)
Background: With aging, the cognitive function of the prefrontal cortex (PFC) declines, postural control weakens, and fall risk increases. As a mind-body exercise, regular Tai Chi practice can improve postural control and effectively prevent falls; however, underlying brain mechanisms remain unclear. We explored possible neurological mechanisms by analyzing the effect of Tai Chi on the PFC of the older adults using functional near-infrared spectroscopy (fNIRS). Methods: 36 healthy older adults without Tai Chi experience were divided randomly into Tai Chi and Control groups. The experiment was conducted four times per week for 16 weeks; 27 participants remained and completed all the experiment procedures. Negotiating obstacle task (NOT) and negotiating obstacle with cognitive task (NOCT) tests were performed pre- and post-intervention, and Brodmann area 10 (BA10) was detected using fNIRS for hemodynamic changes. A three-dimensional motion capture system measured walking speed. Results: After intervention in the Tai Chi group under NOCT, the oxygenated hemoglobin concentration change value (ΔHbO2) in the BA10 was significantly greater (Right BA10: P = 0.002, Left BA10: P = 0.001), the total hemoglobin concentration change value (ΔHbT) in the BA10 was significantly greater (Right BA10: P = 0.006, Left BA10: P = 0.003), walking speed was significantly faster (P=0.040), and dual-task cost was significantly lower than pre-intervenion (P = 0.047). The deoxygenated hemoglobin concentration change value (ΔHbR) had no significant changes (P >0.05). Dual-task cost was negatively correlated with ΔHbO2 (Right BA10: r=-0.443, P=0.021, Left BA10: r=-0.448, P=0.019) and ΔHbT in the BA10 under NOCT (Right BA10: r=-0.417, P=0.031, Left BA10: r=-0.431, P=0.025) respectively. Conclusion: Tai Chi practice might increase cognitive resources of the older adults through the PFC bilateral activation to prioritize gait performance during negotiating obstacles under a dual-task condition.